Neuropeptide S reduces propofol- or ketamine-induced slow wave states through activation of cognate receptors in the rat. (June 2017) - Kong, Xiang-Pan; Wang, Can; Xie, Jun-Fan; Zhao, Peng; Dai, Li-Rong; Shao, Yu-Feng; Lin, Jian-Sheng; Hou, Yi-Ping
Abstract: Intracerebroventricular injection of NPS reduces the duration of the ketamine- or thiopental-induced loss of the righting reflex in rats. But the specific EEG activities are unknown. We therefore sought to examine the effects of the NPS-NPSR system on anesthetic-induced characteristics of EEG power spectra and sleep-wake profiles. NPS alone or together with an NPSR antagonist was injected intracerebroventricularly, whereas the propofol (50 mg/kg) or ketamine (100 mg/kg) was administrated intraperitoneally. NPS (1 or 2 nmol) significantly reduced the amount of propofol-induced EEG delta activity and slow wave states (SWS). NPS (1 or 5 nmol) significantly reduced the amount of ketamine-induced SWS and EEG delta activity. Cortical EEG power spectral analysis showed that, in saline-pretreated rats, propofol induced a marked increase in delta (0.5–4 Hz) activity, decrease in theta (4.5–8.5 Hz) activity, and decrease in high frequency activity (14.5–60 Hz), while, in rats pretreated with 1 nmol of NPS, the duration of delta activity was reduced, while its spectral pattern was not changed. Whereas injection of ketamine into saline-pretreated rats induced a marked increase in delta (0.5–4 Hz) activity, a moderate increase in theta (4.5–8.5 Hz) activity, and a marked decrease in high frequency (14.5–60 Hz) activity. However, delta activity was reduced while theta activity increased under pretreatment with 1 nmol of NPS. The inhibitory effect of NPS on anesthetic-induced SWS was characterized by a reduced SWS episode duration with no significant change in either episode number or latency to SWS. [D-Val 5 ]NPS, an NPSR antagonist (20 nmol), significantly attenuated the arousal-promoting effect of 1 nmol of NPS, but had no effect on SWS when injected alone. We speculate that NPS significantly reduces anesthetic-induced SWS and EEG slow activity by selective activation of the NPSR, which, in turn, would trigger subsequent arousal pathways. Highlights: NPS reduces the amount of propofol- or ketamine-induced SWS. NPS reduces the δ or θ activity induced by propofol or ketamine respectively. NPS, which selective activation of NPSR to produces arousal effects